Examining the Effect of Forensic Accounting Competence on the Detection of Financial Fraud: A Study in Türkiye - ASLAN, Yakup; GÜNGÖR KARYAĞDI, Nazan (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study aims to reveal the leading role of forensic accounting in combating financial corruption, which is one of the main barriers to development. The article aims to show the relationship between improving forensic accounting skills of professionals and the level of prevention of financial corruption. Thus, aim to add depth to literature. The survey first included questions aimed at defining demographic data. To analyze the subject of the research, “Expressions regarding the forensic accounting knowledge and techniques used in detecting and combating corruption” were tested. The third part of the survey included “Expressions regarding the determination of the skills required for accountants using forensic accounting”. The survey items were created using a 5-point Likert scale. Survey items were created based on by utilizing the study conducted by Saleh et al. (2020). In this study, a survey was conduct on CPAs operating in Türkiye (Bitlis, Hakkari, Muş and Van) provinces. In this study, a survey was conducted on 243 CPAs and the results were analyzed. Descriptive analyses were performed on the research data using SPSS version 25.0 program. Structural equation modeling and path analyses were performed using LISREL 8.7 program. The skills required for accountants using forensic accounting have a positive effect of 0.77 units on detecting and combating corruption, meaning that a one-unit improvement in the skills required for accountants using forensic accounting will result in a 0.77-unit increase in the level of detecting and combating corruption. It was determined that 59% of the level of detecting and combating corruption by forensic accountants is explained by the skills required for accountants using forensic accounting.